Сердце в гипсе: роман / К. Грохоля; перевод с польского О. Л. Катречко - Грохоля Катажина (АСТ : Ермак, 2003)
Экземпляры: ф.4 (20140508) / Инвентарный номер: 37061 / Цена: 48 / Авт.знак: Г 89 / ГРНТИ: 17.82 / ББК: 84(4Пол)